Antiviral Effects of Cyclosporin A in Neonatal Mice With Rotavirus-Induced Diarrhea. Issue 1 (January 2015) - Shen, Zigang; Tian, Zhiqiang; He, Haiyang; Zhang, Ji; Li, Jintao; Wu, Yuzhang
ABSTRACT: Objectives: Because rotavirus gastroenteritis is associated with high morbidity and mortality especially in developing countries, it is necessary to develop antirotavirus drugs for the treatment of rotavirus infection. Previous studies have demonstrated that cyclosporin A (CsA) has antiviral properties against rotavirus. Its effect has not yet been evaluated against rotavirus diarrheal disease. The aim of this study was to assess the anti-rotavirus efficacy of CsA in neonatal mice after induction of rotavirus diarrhea. Methods: Suckling mice were inoculated with murine rotavirus. On the onset of diarrhea, mice were given different concentrations of CsA. To evaluate the effects of CsA on reduction of rotavirus diarrhea, diarrhea score, fecal virus shedding, and pathological lesion change in the small intestine, messenger RNA (mRNA) expression levels in the small intestine and spleen of mice were measured for type I interferon (IFN-α and IFN-β), inflammation-related cytokines (interleukin [IL]-8, IL-10, IFN-γ, and tumor necrosis factor-α), and inflammatory signaling pathways (p38, c-Jun N-terminal kinase, activator protein-1, and nuclear factor-kappa B). Results: Among virus-inoculated and CsA-treated groups, a dose of 5 mg · kg −1 · day −1 of CsA inhibited diarrhea and improved fecal virus shedding and intestinal lesion changes. IFN-β mRNA expression was significantly increased in rotavirus-induced diarrhea mice treated with 5 mg · kg −1 · day −1 of CsA, whereas the mRNA expression levels of inflammation-related cytokines (IL-8, IL-10, IFN-γ, and tumor necrosis factor-α) and inflammatory signaling pathways (p38, c-Jun N-terminal kinase, activator protein-1, and nuclear factor-kappa B) were markedly decreased. Antiviral effects of CsA were dose dependent. Conclusions: CsA can inhibit rotavirus infection in neonatal mice through its antiviral properties. The mechanism for this may be through CsA suppression of inflammation by viral inhibition in animal models.